Physical activity and body composition risk for metabolic syndrome - Pratama, Yanasta Yudo; Marfianti, Erlina; Luthfi Adnan, Muhammad; Sava Nuraida, Aisha; Suryalfihro Al-Ghozi, Yasfi; Sukarno, Rizky Triutami (Universitas 'Aisyiyah Yogyakarta, 2024)
Metabolic syndrome is one of the main risk factors for various diseases such as cardiovascular disease and diabetes. The effect of physical activity has been widely studied regarding its benefits in reducing the development of metabolic syndrome. However, there are still underlying shortcomings in the results of previous research. Objective: to assess the influence of physical activity and metabolic syndrome components on the risk of metabolic syndrome in workers. Cross-sectional research was conducted on employees of PT. PLN. Variables assessed include waist circumference, arm circumference, body mass index (BMI), blood pressure, blood glucose and total cholesterol. Physical activity assessment was carried out using the Global Physical Activity Questionnaire (GPAQ). A total of 40 employees were included in this study. A total of 18 respondents (45%) were at risk of metabolic syndrome. The majority of metabolic syndrome components in employees are overweight (50%), excessive arm and waist circumference (85% and 65%, respectively). The majority of respondents had moderate physical activity (57.5%) and high activity (27.5%). Excessive arm and waist circumference had a significant relationship with the risk of metabolic syndrome in respondents (p < 0.05), however, physical activity did not affect the risk of metabolic syndrome. It is hoped that further research in broader populations will be needed to assess risk factors for metabolic syndrome in workers.